1944
DOI: 10.1017/s0022029900003861
|View full text |Cite
|
Sign up to set email alerts
|

308. The freezing-point of milk: II. The influence of various factors and their bearing on the detection of added water

Abstract: The results of a series of determinations of the freezing-point depressions of the milk of the individual cows of a Shorthorn herd over a period of 16 months are reported.The relative constancy of the freezing-point was confirmed, all but two values deviating by less than 4·5% from the mean Δ values.Significant seasonal trends were observed, especially during the spring when the supply of ample amounts of young grass may cause the production of milk with somewhat smaller freezing-point depressions.Systematic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1944
1944
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Regan and Richardson observed that changes in environmental temperature affected the freezing point [27]. Aschaffenburg and Veinoglou suggested that differences in environmental temperature were a contributing factor to the seasonal variations that they observed [28].…”
Section: Follow-up Freezing Point 2015-2016mentioning
confidence: 96%
“…Regan and Richardson observed that changes in environmental temperature affected the freezing point [27]. Aschaffenburg and Veinoglou suggested that differences in environmental temperature were a contributing factor to the seasonal variations that they observed [28].…”
Section: Follow-up Freezing Point 2015-2016mentioning
confidence: 96%
“…However, most work has had as its aim the use of the constant for the detection of added water, and less information is available regarding the partial contributions of different constituents and the inter-relationships of these partial contributions. Surveys of a general nature have been carried out by Aschaffenburg & Temple (8), who did not find a close correlation between solids-not-fat and freezing-point depression over a full lactation period, and by Aschaffenburg & Veinoglou (9), who reported normal freezingpoint depressions with low solids-not-fat content. Scott-Dodd & Cowan (10) and Rowland, Aschaffenburg & Veinoglou(ii) have reported similarly on samples from cows infected with mastitis.…”
mentioning
confidence: 99%
“…(**) Existe diferença entre os métodos ao nível de 1% e 5% de probabilidade. (Sato, Hankinson, Gould, & Armstrong, 1957;Shipe, Dahlberg, & Herrington, 1953;Arlington, & Krienke, 1949;Aschaffenburg, & Veinoglou, 1944). De acordo com a legislação brasileira…”
Section: Diferença Entre As Proporções P-valor Intervalo De Confiançaunclassified